Association of ventilation mode and indoor CO2 concentration with indoor bacterial communities in Singapore childcare centres - Chai, Ming Rher (Nanyang Technological University, 2024)
Poorly ventilated indoor spaces may increase airborne pathogen transmission risk. This study aims to investigate the association of ventilation mode and indoor CO2 concentration with indoor bacterial communities in Singapore childcare centres. Air samples collected from 12 different childcare centres in Singapore was subjected to metagenomic sequencing to determine its bacterial community. The childcare centres were grouped according to their ventilation modes. Output from metagenomic sequencing was presented in MetaGenome Analyser (MEGAN) file which was used for bioinformatics analysis. Principal coordinate analysis (PCoA) graph, Alpha-diversity graph and Operational taxonomic unit (OTU) graph was plotted using information derived from MEGAN and used to study the differences in bacterial community between childcare centres with different ventilation mode. Mechanical ventilation systems may effectively reduce the indoor bacterial diversity as compared to other ventilation modes due to lower diversity and OTU observed. Different ventilation adequacies between childcare centres with same ventilation modes was observed to have an effect on the indoor bacterial diversity, suggesting ventilation adequacy might have a role in influencing the bacterial community. Initial findings suggests that there may be an association of ventilation modes and CO2 concentration with indoor bacterial community. Larger scale research is needed for validation of results.